Unpunished - Black, Lisa, 1963- (Black, Lisa, 1963- Gardiner and Renner thriller., 2017)
Forensic expert Maggie Gardiner continues her uneasy partnership with vigilante homicide detective Jack Renner to investigate the murder of a newspaper copy editor.